Lagerstroemia x 'Apalachee' Apalachee Crape Myrtle: FPS-323/FP323, 5/2007 - Gilman, Edward (EDIS, 2007)
This document provides an overview of the ‘Apalachee’ crape myrtle (Lagerstroemia x ‘Apalachee’), highlighting its features, planting requirements, and uses. The tree is noted for its striking summer flowers, attractive fall foliage, and high drought tolerance. It thrives in USDA hardiness zones 7 through 9A and is suitable for various urban and suburban landscaping applications. The document also discusses the tree’s growth habits, soil and light preferences, pruning guidelines, and pest resistance. Additionally, it mentions several cultivars with varying flower colors and disease resistance.